Legal Consequences of Forgery of Authentic Deeds on the Legal Validity of the Deed - Faizeh, Nurul; Latumahina, Rosalinda Elsina (CV. Era Digital Nusantara, 2024)
In the context of law enforcement, a notary is a public official who works in the legal industry and contributes to societal legal certainty. According to Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notary, a notary is a state organ authorized by the state (hence abbreviated as UUJN). There is legal confusion for notaries in the event that they make mistakes in the performance of their responsibilities and authorities due to the overlap between the application of criminal law governed in the Penal Code (KUHP) and the UUJN. According to UUJN, a notary may face civil, administrative, or ethical code of the notary profession sanctions if they violate the law while performing their duties. The purpose of this study is to comprehend and clarify the legal ramifications of authentic deed forging on the deed's legal validity as well as the criminal responsibility of notaries who engage in this practice. This study employed a normative, legislative, and conceptual approach as its methodology. The findings of this study suggest that the legal ramifications of forging authentic deeds on their legal validity are as follows: if a prerequisite for the deed's creation is not fulfilled, it will lose its uniqueness and be deemed legally defective, meaning it will be deemed invalid and have no valid probative value.